Pengaruh Islamic Corporate Governance, Sharia Complience dan Islamic Social Reporting Terhadap Kinerja Keuangan Perbankan Syariah - Novitri, Revista Williya; Adi, Suyatmin Waskito (Jurnal EMT KITA, 2024)
This research aims to determine the influence of Islamic Corporate Governance, Sharia Complience and Islamic Social Reporting on the Financial Performance of Indonesian Sharia Banking. This research uses secondary data in the form of company annual reports. The sample used in this research was Sharia Commercial Banks registered with the financial services authority in 2018 - 2022. From this research, 35 samples were obtained that met the criteria. The analytical method used is multiple linear regression analysis. The results of this research are that Islamic Corporate Governance, Zakat Performance Ratio, Islamic Social Reporting have an effect on the financial performance (ROA) of sharia commercial banks, while the Profit-Sharing Ratio has no effect on the financial performance (ROA) of sharia commercial banks.